Integrity and Internal Control in Information Systems VI IFIP TC11 / WG11.5 Sixth Working Conference on Integrity and Internal Control in Information Systems (IICIS) 13–14 November 2003, Lausanne, Switzerland - Jajodia, Sushil; Strous, Leon (Springer US, 2004)
The development and integration of integrity and internal control mechanisms into information system infrastructures is a challenge for researchers, IT personnel and auditors. Since its beginning in 1997, the IICIS international working conference has focused on the following questions: what precisely do business managers need in order to have confidence in the integrity of their information systems and their data and what are the challenges IT industry is facing in ensuring this integrity; what are the status and directions of research and development in the area of integrity and internal control; where are the gaps between business needs on the one hand and research / development on the other; what needs to be done to bridge these gaps. This sixth volume of IICIS papers, like the previous ones, contains interesting and valuable contributions to finding the answers to the above questions. We want to recommend this book to security specialists, IT auditors and researchers who want to learn more about the business concerns related to integrity. Those same security specialists, IT auditors and researchers will also value this book for the papers presenting research into new techniques and methods for obtaining the desired level of integrity
Keywords: Cryptology; Management of Computing and Information Systems; IT in Business; Software Engineering/Programming and Operating Systems; Accounting/Auditing; Data encryption (Computer science); Management information systems; Computer science; Information technology; Business—Data processing; Software engineering; Accounting; Bookkeeping; Konferenzschrift